2018
DOI: 10.1186/s12911-018-0641-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of binary digital region asymmetry with application to skin lesion detection

Abstract: BackgroundThe performance of Computer Aided Diagnosis Systems for early melanoma detection relies mainly on quantitative evaluation of the geometric features corresponding to skin lesions. In these systems, diagnosis is carried out by analyzing four geometric characteristics: asymmetry (A), border (B), color (C) and dimension (D). The main objective of this study is to establish an algorithm for the measurement of asymmetry in biological entities.MethodsBinary digital images corresponding to lesions are divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Then, both images were divided into eight parts to assess the shape and color asymmetry of the skin lesion (see Figure 3). Indeed, according to the ABCDE rule [23] and following the parameters extracted by Bhuiyan et al [24], the following image features were collected (see The work by Dalila et al [25] showed that most of the relevant features for skin lesion classification are related to color variation; hence, we paid more attention to that type of features. To extract the colors from the images, the K-means algorithm was applied.…”
Section: Feature Extraction and Classificationmentioning
confidence: 99%
“…Then, both images were divided into eight parts to assess the shape and color asymmetry of the skin lesion (see Figure 3). Indeed, according to the ABCDE rule [23] and following the parameters extracted by Bhuiyan et al [24], the following image features were collected (see The work by Dalila et al [25] showed that most of the relevant features for skin lesion classification are related to color variation; hence, we paid more attention to that type of features. To extract the colors from the images, the K-means algorithm was applied.…”
Section: Feature Extraction and Classificationmentioning
confidence: 99%
“…The second characteristic obtained is the irregularity of the edges that could exist, for this we analyze the edge of the mole. The same procedure as Sancen-Plaza et al in [23] is followed with the area obtained in the process of application (10) shown in Figure 10(b). From this process, 9 descriptors of the degree of irregularity of the border are obtained, according to Santiago-Montero et al [24].…”
Section: Bordermentioning
confidence: 99%